226k views
1 vote
Find the average rate of change of the function below from x1 to x2.

f(x)=2x+7

from

x1=−1

to

x2=0

Question 9 options:

a)

2

b)

−12

c)

13

d)

-8

e)

none

User Alex Shyba
by
4.6k points

2 Answers

1 vote

Answer:

wala akong alam jun

Explanation:

i hate math, mathuloggggggg ka, ayieee ?luh asa ka

User Slim Fadi
by
4.8k points
5 votes

Answer:

The average rate of change is 2, letter a)

Explanation:

Given a function y, the average rate of change S of y=f(x) in an interval
[x_(s), x_(f)] will be given by the following equation:


S = (f(x_(f)) - f(x_s))/(x_(f) - x_(s)).

In our problem, we have that:


f(x) = 2x + 7


x_(s) = -1


x_(f) = 0

So:


f(x_(s)) = f(-1) = 2(-1) + 7 = -2 + 7 = 5


f(x_(f)) = f(0) = 2(0) + 7 = 0 + 7 = 7

The average rate of change is:


S = (f(x_(f)) - f(x_s))/(x_(f) - x_(s)) = (7-5)/(0 -(-1)) = (2)/(1) = 1

The average rate of change is 2, letter a)

User Vishal Ranapariya
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.